208k views
0 votes
X − 3 − 2(6 − 2x) = 2(2x − 5)

2 Answers

3 votes

Answer: X = 5

Explanation:

x - 3 - 2(6-2x) = 2(2x-5)

x - 3 - (12-4x) = (4x-10)

Simplify

5x - 15 = 4x - 10

Then move to common sides giving you the answer

X = 5

User Pete Alvin
by
5.9k points
2 votes

Multiply the first bracket by -2

Multiply the second bracket by 2

x-3-12+4x= 4x-10

- negative number times + positive number= - negative number

- negative number times -negative number = + positive number

x+ 4x-3-12= 4x-10

5x-15= 4x-10

Move 4x to the other side

5x-4x-15= 4x-4x-10

x-15= -10

Move -15 to the other side

x-15+15= -10+15

x= 5

Answer : x= 5

User Kishan Vaghela
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.